Strengthening the School Literacy Movement: The Utilization of Literacycloud.com Technology to Improve Students' Interest in Reading - Faizah, Rohmatul; Baedowi, Ahmad; Fadil, Cholid; Rifqi Rizqullah Ghozalie, Mohammad (International Journal of Educational Research & Social Sciences, 2022)
A great nation is a nation that not only utilizes its natural resources but also develops other potentials such as reading and writing as a bridge of civilization from one generation to another. Nowadays, technology is commonly used in all fields, including education, to increase the reading interest among students that are still very low. The School Literacy Movement (Gerakan Literasi Sekolah or GLS) is part of the implementation of the Regulation of the Minister of Education and Culture Number 23 the Year 2015 concerning "Business Character Development." It aims to foster a literacy culture and increase interest in reading, critical thinking, and problem-solving. This study aims to reveal the use of technology to support the policy of the school literacy movement using Literacycloud.com at SDN Nglumber II Kepohbaru Bojonegoro. The method used is descriptive qualitative with data sources in the form of interviews, literature reviews, field notes, and observations. The results showed that using Literacycloud technology synergized with the GLS policy program at SDN Nglumber II Kepohbaru Bojonegoro could improve students' reading interest. In addition, there are also inhibiting factors for the GLS program at SDN Nglumber II Kepohbaru Bojonegoro, including inadequate books and library space, the absence of a GLS bureaucratic structure, and low student awareness of reading.